Pengaruh Pengetahuan Pajak, Sanksi Pajak, dan Modernisasi Sistem pada Kepatuhan Wajib Pajak - Mulyadin, Slamet; Anasta, Lawe (Penerbit Goodwood, 2024)
Purpose: This research aims to examine the influence of tax knowledge, tax sanctions and system modernization on MSME taxpayer compliance in the East Cengkareng area, West Jakarta. Methodology/Approach: This study used a quantitative approach with data collection techniques by distributing questionnaires and observations. The sample in this study comprised 100 MSME taxpayer respondents who met the criteria for having the largest NPWP in East Cengkareng. A random sampling method was used in this study. Hypothesis testing was performed using multiple linear regression analysis. Results: This study shows that tax knowledge influences taxpayer compliance. Tax sanctions affect taxpayer compliance, and system modernization has no effect on taxpayer compliance. Limitations: The results of this study may only apply to the East Cengkareng area in West Jakarta, and cannot be directly generalized to other regions or the general population. Contribution: This means that taxpayers’ tax knowledge regarding taxation will guarantee that they will be more compliant in carrying out their tax obligations.